Higher Incidence of Atrial Fibrillation in Left Ventricular-to-Right Atrial Shunt Patients - Chou, Hongda; Chen, Hongxia; Xie, Juan; Xu, Aiqing; Mu, Guanyu; Han, Fei; Tse, Gary; Li, Guangping; Liu, Tong; Fu, Huaying (Frontiers in Physiology, 2020)
Background: The possible association between atrial fibrillation (AF) and left ventricular-to-right atrial shunt (LVRAS) has never been reported yet. The present study investigated the incidence of AF in LVRAS. Methods: This was a retrospective study of consecutive patients undergoing echocardiography at a single tertiary center. Clinical data, laboratory results and echocardiography parameters such as right atrial area (RAA), right ventricular end diastolic diameter (RVDD) and left atrial diameter (LAD) were compared between LVRAS group and non-LVRAS patients, and between AF and non-AF patients. Propensity score matching was performed to decrease the effect of confounders. Logistic regression analysis and mediation analysis were used to estimate the relationship between LVRAS and AF. Results: A total of 3,436 patients were included, and the incidence of LVRAS was 1.16% (n = 40). The LVRAS group had significantly larger RAA, RVDD and LAD compared with non-LVRAS group. Those who suffered from AF showed larger RAA, RVDD and LAD compared with those who maintained sinus rhythm. Multivariable logistic regression showed that gender (OR: 0.608), age (OR: 1.048), LAD (OR: 1.111), mean pulmonary artery blood pressure (mPAP, OR: 1.023), TR (OR: 2.309) and LVRAS (OR: 12.217) were significant factors for AF. RAA could partially mediate the relationship between LVRAS and AF according to the result of mediation analysis. Conclusions: Our study suggested that LVRAS, TR, LAD, mPAP, age and male were risk factors for AF. RA enlargement might underlie mechanism in the higher incidence of AF in LVRAS patients. These findings should be confirmed in larger prospective studies.